Emaze App as an Assistive Tool in Cultural Arts Learning - Muhamad Fadli; Darmawati (Universitas Negeri Padang, 2024)
The purpose of this study was to test the use of the Emaze application as a tool in learning Cultural Arts (Dance) at SMK Pariwisata Aisyiyah West Sumatra. This research adopts a quantitative approach with a Pre-Experimental Design design. Researchers themselves act as research instruments, supported by tools such as cameras and indicator sheets. The study population consisted of 11 grade X students at SMK Pariwisata Aisyiyah West Sumatra. Research samples were selected using the group or cluster sampling method. Data was collected through dance creativity tests, observation, and interviews. The data analysis steps include the stages of data clarification, data description, and drawing conclusions. The results indicate that the use of the Emaze application has a positive effect on increasing the creativity of dance movements in grade X students of SMK Tourism Aisyiyah West Sumatra. This resulted in increased achievement in Cultural Arts learning. Student learning creativity is also increased thanks to the use of 2D to 3D visual features from the Emaze application. This effectiveness is evident from the results of student practice examinations that achieve satisfactory results and are in accordance with the learning objectives as stated in the teaching module. The teacher also appreciated the use of the Emaze application as a tool in learning Cultural Arts (Dance) and showed interest in better understanding its use and integrating it through discussion methods in teaching.